Spillover effects from euro area monetary policy across the EU: A factor-augmented VAR approach - Galina Potjagailo (Kiel Institute for the World Economy (IfW), 2016)
I analyze spillover effects from Euro area monetary policy shocks to thirteen EU countries outside the Euro area, i.e., ten countries from Central and Eastern Europe (CEE) and three Western EU members. The analysis is based on a FAVAR model with two blocks which exploits a large cross-country data set covering real activity variables, prices and financial variables. An expansionary Euro area monetary policy shock raises production in most non-Euro area countries. Somewhat larger and more instantaneous responses of production are observed in small open economies with fixed exchange rate regimes, where foreign demand effects are particularly strong. In addition, a Euro area monetary expansion leads to declines in interest rates and reductions in uncertainty in most non-Euro area countries. The spillovers on uncertainty are more pronounced in economies with flexible exchange rates, where the degree of financial market openness tends to be higher and where exchange rate appreciations further enhance risk taking by cushioning debt burdens from foreign currency loans. Finally, spillover effects on prices are heterogeneous across countries and behave asymmetrically in most CEE countries.
Keywords: C33; E52; E58; F42; 330; monetary policy; Euro area; Central and Eastern Europe; exchange rate regime; financial transmission; FAVAR